A novel deletion of exon 4 in the Ectodysplasin A gene associated with X-linked hypohidrotic ectodermal dysplasia. (June 2023) - Agiannitopoulos, Konstantinos; Potska, Kevisa; Douka, Anna; Gintoni, Iphigenia; Tsaousis, Georgios N.; Papadopoulou, Eirini; Nasioulas, George; Yapijakis, Christos
Abstract: Objective: Identify the disease-causing mutation in a patient with features of X-linked hypohidrotic ectodermal dysplasia, which is a genetic disorder characterized by hypodontia, hypohidrosis and hypotrichosis. It is caused by mutations in Ectodysplasin A gene, which encodes ectodysplasin A, a member of the tumor necrosis factor superfamily. Design: Genetic analysis, was performed using chromosomal microarray analysis, whole exome sequencing and multiplex ligation-dependent probe amplification analysis in a 4-year-old boy with hypohidrotic ectodermal dysplasia features. Moreover, the boy's parents were tested for clinically significant findings identified in order to elucidate the pattern of inheritance of the finding detected in the proband. Results: A novel deletion of entire exon 4 in Ectodysplasin A gene identified in the 4-year-old patient. This deletion was found in heterozygous state in the mother of the proband and was not detected in his father. RNA analysis revealed an in-frame deletion r.527_706del, p.(176_236del) in exon 4 of the Ectodysplasin A gene. Conclusion: We identified a novel gross deletion in the Ectodysplasin A gene in a male patient with X-linked hypohidrotic ectodermal dysplasia. Clinical and molecular genetic analysis are crucial to set an accurate diagnosis in patients with hypohidrotic ectodermal dysplasia. These results highlight the importance of the collagen domain of Ectodysplasin A, encoded by exon 4, for its function in vivo. Highlights: ● A novel deletion of the entire exon 4 of Ectodysplasin A gene was identified. ● The variant was found in hemizygous state in a patient with HED features. ● The Ectodysplasin A deletion was inherited from the pre-symptomatic mother. ● Copy number variation analysis is essential for accurate diagnosis of X-linked HED.